John Calvin on the gifts of the Holy Spirit in his commentary on Acts - Alten, H. H. van (2017)
John Calvin is often considered to have taught the cessation of the extraordinary gifts of the Holy Spirit. This certainly does not give the complete picture of how Calvin wrestled with those passages from Scripture which deal with the extraordinary gifts. In his commentary on the book of Acts Calvin makes a conscious effort to show that in most of the cases where the gifts of the Spirit are mentioned, the focus is not on the gifts in a general sense, but in an extraordinary sense. These extraordinary gifts had been limited to the initial phase of the church. The reasons that Calvin provides for this cessation is somewhat ambiguous. On the one hand Calvin indicates a very specific, divine purpose for the gifts, which limits its usefulness and existence until the point when the purpose had been achieved. However, there are also passages where one gets the impression that the cessation of the gifts was not necessarily divinely intended, but was due to human error. Of great importance is the way Calvin subsequently applies these texts to the readers of his own day.
Johannes Calvyn oor die gawes van die Heilige Gees in sy kommentaar op HandelingeDikwels word aangeneem dat Johannes Calvyn die beëindiging van die buitengewone gawes van die Heilige Gees voorgestaan het. Dit gee egter nie die volle prentjie van hoe Calvyn met daardie Skrifgedeeltes, waarin die buitengewone gawes behandel word, geworstel het nie. In sy kommentaar op die boek Handelinge wys Calvyn bewustelik daarop dat in die meeste gevalle waar die gawes van die Gees genoem word, die fokus nie op die gawes in 'n algemene sin is nie, maar eerder op die gawes in 'n buitengewone sin. Hierdie buitengewone gawes is beperk tot die beginfase van die kerk. Die redes wat Calvyn vir hierdie beëindiging aanvoer, is egter dubbelsinnig. Aan die eenkant wys Calvyn op 'n baie spesifieke, Goddelike doel met die gawes, waardeur hulle bruikbaarheid en voortbestaan beperk word tot die tyd toe die doel bereik is. Aan die anderkant, egter, is daar ook gedeeltes wat die indruk skep dat die beëindiging van die gawes nie noodwendig Goddelik bepaal is nie, maar 'n gevolg was van menslike sonde. Van groot belang is hoe Calvyn hierdie tekste vervolgens toepas op die lesers van sy eie tyd.
Keywords: Acts of the Apostles; GIFTS OF THE SPIRIT; John Calvin; Prophecy